Expansion of the phenotypic spectrum of de novo missense variants in kinesin family member 1A (KIF1A). Issue 10 (22nd July 2020) - Kaur, Simranpreet; Van Bergen, Nicole J.; Verhey, Kristen J.; Nowell, Cameron J.; Budaitis, Breane; Yue, Yang; Ellaway, Carolyn; Brunetti‐Pierri, Nicola; Cappuccio, Gerarda; Bruno, Irene; Boyle, Lia; Nigro, Vincenzo; et al.
Abstract: Defects in the motor domain of kinesin family member 1A ( KIF1A ), a neuron‐specific ATP‐dependent anterograde axonal transporter of synaptic cargo, are well‐recognized to cause a spectrum of neurological conditions, commonly known as KIF1A ‐associated neurological disorders (KAND). Here, we report one mutation‐negative female with classic Rett syndrome (RTT) harboring a de novo heterozygous novel variant [NP_001230937.1:p.(Asp248Glu)] in the highly conserved motor domain of KIF1A. In addition, three individuals with severe neurodevelopmental disorder along with clinical features overlapping with KAND are also reported carrying de novo heterozygous novel [NP_001230937.1:p.(Cys92Arg) and p.(Pro305Leu)] or previously reported [NP_001230937.1:p.(Thr99Met)] variants in KIF1A . In silico tools predicted these variants to be likely pathogenic, and 3D molecular modeling predicted defective ATP hydrolysis and/or microtubule binding. Using the neurite tip accumulation assay, we demonstrated that all novel KIF1A variants significantly reduced the ability of the motor domain of KIF1A to accumulate along the neurite lengths of differentiated SH‐SY5Y cells. In vitro microtubule gliding assays showed significantly reduced velocities for the variant p.(Asp248Glu) and reduced microtubule binding for the p.(Cys92Arg) and p.(Pro305Leu) variants, suggesting a decreased ability of KIF1A to move along microtubules. Thus, this study further expanded the phenotypic characteristics of KAND individuals with pathogenic variants in the KIF1A motor domain to include clinical features commonly seen in RTT individuals. Abstract : KIF1A‐associated Neurological Disorders (KANDs): functional validation of identified variants.